2012
DOI: 10.1159/000342170
|View full text |Cite
|
Sign up to set email alerts
|

Impact of National Income and Inequality on Sugar and Caries Relationship

Abstract: Objective: The aim of this study was to examine the impact that national income and income inequality in high and low income countries have on the relationship between dental caries and sugar consumption. Methods: An ecological study design was used in this study of 73 countries. The mean decayed, missing, or filled permanent teeth (DMFT) for 12-year-old children were obtained from the WHO Oral Health Country/Area Profile Programme. United Nations Food and Agricultural Organization data were used for per capit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 42 publications
2
42
0
2
Order By: Relevance
“…Effects of wartime sugar rationing and sanctions Meta-analyses confirm the statistical relationship between the average sugar intakes and the prevalence of caries (4,28,29) , reinforcing the ecological studies with in effect national interventions induced by wartime sugar rationing and sanctions on sugar imports. Iraq (21) showed the marked responsiveness of caries to prevailing sugar intakes: levels of dental caries in Iraqi children halved after UN sanctions that reduced sugars from 50 kg/capita per year (27·4 %E) before sanctions to 12 kg/capita per year (6·6 %E) five years later (Table 1) (21) .…”
Section: Studies In Populations With Low Sucrose Intakesmentioning
confidence: 58%
“…Effects of wartime sugar rationing and sanctions Meta-analyses confirm the statistical relationship between the average sugar intakes and the prevalence of caries (4,28,29) , reinforcing the ecological studies with in effect national interventions induced by wartime sugar rationing and sanctions on sugar imports. Iraq (21) showed the marked responsiveness of caries to prevailing sugar intakes: levels of dental caries in Iraqi children halved after UN sanctions that reduced sugars from 50 kg/capita per year (27·4 %E) before sanctions to 12 kg/capita per year (6·6 %E) five years later (Table 1) (21) .…”
Section: Studies In Populations With Low Sucrose Intakesmentioning
confidence: 58%
“…The authors suggested as possible explanation for the anomalous association of low mean DMFT with high sugar disappearance in Western Europe that the extensive use of, mainly fluoride-containing, toothpastes neutralise the potential damage from high sugar consumption [Downer et al, 2008]. A recent global evaluation [Masood et al, 2012] confirmed that among high-income countries, there is a negative correlation between sugar disappearance (kg/capita/year) and dental caries level, while in low-income countries, this correlation is a positive one. In the ensuing discussion, Masood et al (2012) explain their findings by the accessibility to fluoride.…”
Section: Dose Response Curve Between Sugar Consumption and Cariesmentioning
confidence: 99%
“…This is attributed to increasing sugar consumption and lack of fluoride [8,9,21]. In our study, the major cause of admission to hospital of the children was tooth decay with 25%.…”
Section: Discussionmentioning
confidence: 63%